13.4k views
2 votes
Given: f(x) = 2x + 5 and g(x) = x2 and h(x) = -2x h(g(f(x))) = x² + x +

User Thamurath
by
5.0k points

2 Answers

3 votes

Answer:


\Large \boxed{h(g(f(x)))=-8x^2-40x-50}

Explanation:


f(x)=2x+5 \\\\ g(x)=x^2 \\\\h(x)=-2x


h(g(f(x)))=-2((2x+5)^2)

Expanding and solving for brackets.


h(g(f(x)))=-2(4x^2+20x+25)

Distributing -2 to the terms in the brackets.


h(g(f(x)))=-8x^2-40x-50

User NeatNerd
by
4.4k points
3 votes

Answer:

-8x^2 - 40x - 50

Explanation:

f(x) = 2x + 5

g(x) = x^2

h(x) = -2x

h(g(f(x))) =

First find g(f(x))

g(f(x)) = (2x+5) ^2 = 4x^2 + 10x + 10x +25

= 4x^2 + 20x + 25

The stick this in for g(f(x)

h(g(f(x))) = -2 (4x^2 + 20x + 25)

= -8x^2 - 40x - 50

User Dive
by
5.4k points